Determinants of Hypertension in Diabetes Patients in Rural Indonesia: The Role of Age and Body Mass Index - Ainun Ni'mah Syawaliyah; Yusuf Alam Ramadhon; Aurora Revi Samantha; Pradestya Achmad Sulthon; Anggita Khoirunnisa Middyana; Muhammad Kevin Samudra (Indonesian Journal of Global Health Research, 2026)
Hypertension is a global health problem and a significant contributor to cardiovascular morbidity and mortality. In Indonesia, the prevalence of hypertension is increasing due to demographic and epidemiological changes. Multifactorial factors such as age, gender, body mass index, population density, and level of industrialization, this risk is especially seen in patients with Type 2 Diabetes Mellitus (T2DM). To assess demographic (age, gender), anthropometric (BMI), and environmental factors and their contribution to the prevalence of hypertension in patients in Gatak District, Sukoharjo Regency. A large-scale case-control study involving secondary data was conducted. Data were accessed from the Gatak Community Health Center management system (SIMPUS). The case group consisted of patients with T2DM and secondary hypertension. The control group consisted of patients who underwent routine check-ups (ICD-10: Z00) without hypertension and diabetes. Participants were selected through specific procedures and inclusion criteria were age 18 years and above and complete medical records, a total of 1,108 participants were analyzed using chi-square and t-test, followed by multivariate logistic regression. The majority of participants were women (65.2%), aged > 45 years (56.4%), and had normal body weight (63%). Multivariate analysis showed that age ≥ 45 years significantly increased the risk of hypertension (p=0.000), and being overweight was also associated with an increased risk (p=0.000). However, gender, population density, and the presence of a manufacturing industry were not significantly associated with hypertension. The most significant predictors of hypertension were age and body mass index, while environment and gender were not associated.